2017
DOI: 10.1111/jth.13547
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in the presence of neutral protamine Hagedorn insulin: a new feature of antibodies against protamine/heparin complexes

Abstract: T. Platelet activation in the presence of neutral protamine Hagedorn insulin: a new feature of antibodies against protamine/heparin complexes.J Thromb Haemost 2017; 15: 176-84. Essentials• Protamine (PRT) is used to stabilize insulin in neutral protamine Hagedorn (NPH) insulin.• The interaction between NPH-insulin, anti-PRT/heparin antibodies and platelets was investigated.• Anti-PRT/heparin antibodies activate platelets in presence of NPH-insulin dependent on heparin.• Cross-reactivity seems to have no major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The expression of CD62P was determined by flow cytometry using a FITC‐labelled anti‐CD62P antibody (CLB‐Thromb/6, Beckman Coulter). Fresh PLTs, used as positive control, were isolated from human blood anticoagulated with acid‐citrate dextrose (ACD, Vacutainer, Becton Dickinson) and resuspended in Tyrode‐buffer, as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…The expression of CD62P was determined by flow cytometry using a FITC‐labelled anti‐CD62P antibody (CLB‐Thromb/6, Beckman Coulter). Fresh PLTs, used as positive control, were isolated from human blood anticoagulated with acid‐citrate dextrose (ACD, Vacutainer, Becton Dickinson) and resuspended in Tyrode‐buffer, as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Pouplard et al 1 found that ;29% (17 of 59) of patients with anti-PRT/heparin antibodies had a positive serotonin release assay in the presence of PRT alone. Recently, Zollner et al 19 noted that 21 (;29%) of 80 sera containing anti-PRT/heparin bound to platelets in the presence of neutral protamine hagedorn insulin, but not in the presence of insulin alone, and that heparin dissociated antibody binding from platelets, implying that PRT was bound to cellular GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…Aż 10% hospitalizowanych wykazało obecność PIT abs, mimo nieodnotowanej ekspozycji na protaminę podczas zabiegów kardiochirurgicznych. PIT abs w sposób zależny od heparyny aktywują płytki krwi w obecności insuliny NPH [28]. Lee i wsp.…”
Section: Czynniki Ryzyka Trombocytopenii Indukowanej Protaminąunclassified